Identifikasi dan Eksplorasi Potensi Pengendalian Invasi Lobster Air Tawar Red Claw di Kota Dumai Untuk Usaha Mikro, Kecil dan Menengah - Freddy Hasiholan Sidauruk; Christ Windreis; Benny Syofyan; Roni Saputra; Rika Sari H. S; Romi Romi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study is part of a relay activity to explore local economic potentials, the discussion of which is focused on identifying and exploring the potential of a resource object selected based on the availability of the resource object and the minimal use of the resource from a business perspective by the local community. The resource object that will be discussed in this case is local fisheries resources in Dumai City, especially fisheries resources from the red claw crayfish commodity or also known as red claw crayfish (Cherax quadricarinatus) which is found in many natural environments in several waterways and river in Dumai City. Exploration of economic use by local communities in this study is also directed as an effort to control the spread of red claw freshwater lobsters which are feared to cause damage to native freshwater biota in Dumai City. Keyword : Dumai City, UMKM, Red Claw Crayfish